Activity of Hydroxymethylpyrimidine Kinase/Thiamine-Phosphate Pyrophosphorylase during Rice Grain Development - Phosaeng, Monthani; Chaicharoen, Rachada; Phraprasert, Phakpoom (Burapha Science Journal, 2024)
Background and Objectives : Thiamine, or vitamin B1 is an essential for human body functions and can be found in foods including rice, cereals, meat, and egg yolk. Rice is one of a staple carbohydrate for 50% of world population, especially in Asia. The amount of thiamine in rice varies among different varieties. As a result, Thiamine content in brown rice was studied to access the variation among rice varieties. Hydroxymethylpyrimidine kinase/thiamine-phosphate pyrophosphorylase (HMPPK/TMP-PPase) is one of key enzymes in thiamine biosynthesis. Consequently, HMPPK/TMP-PPase activity was investigated to better understand the level and pattern of this enzyme in rice grain during four developmental stages. Methodology : Three varieties of rice, RD11, RD43, and Suphanburi 1 (SPR1), were grown in the same environment and time frame. Brown rice was collected at the harvest stage and then extracted by water and used to determine the thiamine content by high performance liquid chromatography. Additionally, the HMPPK/TMP-PPase was extracted and determined the activity in rice grain at four developmental stages: flowering, milky, dough, and harvest. Main Results : The result showed different varieties accumulate statistic significantly different thiamine content (Tukey HSD, P£0.05). RD11 had the highest thiamine content at 97 ng/grain followed by SPR1 with 81 and 74 ng/grain, respectively. This experiment can categorized rice of this studied into 2 groups: high thiamine content (RD11) and lower thiamine content (SPR1 and RD43). The study of HMPPK/TMP-PPase activity revealed a consistent pattern across all 3 varieties. The HMPPK/TMP-PPase activity was lowest during the flowering, increased during milky, reached its highest level during the dough stage, and then decreased at harvest stage, both per grain and per protein basis. The average HMPPK/TMP-PPase activity across all grain developmental stages was highest in RD11 (0.37 n mole/mg protein/min), compared to SPR1 and RD43 (0.20 and 0.13 n mole/mg protein/min, respectively). Conclusions : The activity of HMPPK/TMP-PPase varied among the developmental stages of rice grain. The activity of this enzyme was correlated with the thiamine content in 3 rice varieties. These findings will be valuable data for the breeder aiming to develop rice varieties with high thiamine content.